Contributions of Procedural Memory to Emergent Reading in Older Children - Hannon, Joelle; Zinszer, Benjamin; Kouadio, Elise; Tanoh, Fabrice; Earle, Sayako; Jasińska, Kaja (My University, 2023)
Research on emergent reading has focused almost exclusively on children who begin learning to read by age 5-6, despite the fact that many children around the world begin learning to read later in childhood. Little is known about how older children learn to read for the first time. Importantly, procedural learning supports children’s ability to acquire new skills implicitly and apply those skills with automaticity. Procedural learning is therefore thought to support early reading and reading-related skills, such as phonological awareness. However, as children age they may become less reliant on procedural learning. Older children learn new language skills through largely explicit memorization as opposed to implicit procedural learning, and the same is potentially true for language adjacent skills such as reading. Older children may rely less on procedurally supported phonological awareness when reading for the first time and instead rely on explicit skills such as vocabulary. We examined the role of procedural learning in emergent reading across different ages (9-15 years), focusing on low-literacy communities in rural Côte d’Ivoire, where many children remain in emergent stages of reading even at the end of primary school and age for grade is highly variable. We find that the relation between phonological awareness and reading, and vocabulary and reading among older emergent readers depends on procedural learning.
Supplemental Materials: https://osf.io/qepjr/
Keywords: Adolescence; Emergent Literacy; Memory; Sub-Saharan West Africa